Microbiota-based therapies for chronic kidney disease - Dessy Natasha Ade Putri; Chika Christianne Moreen Nababan (DiscoverSys Inc., 2019)
Background: Increasing prevalence of chronic kidney disease (CKD) worldwide has been concerned as a global public health issue because of the burden of adverse outcomes, including mortality. Gut microbiota can be used as a potential therapeutic target to slow the progression of CKD.Aim: This literature review aims to provide an in-depth review about the potency of microbiota-based therapy for CKD.Method: from 58 journals reviewed, 51 were found suitable as references for this paper. The keywords used are â€œgut microbiota,â€ â€œchronic kidney diseaseâ€, â€œprebioticâ€, â€œprobioticâ€ and â€œfecal microbiota transplantationâ€ on selected search engines.Result: In general, it has shown that microbiota-based therapies do have potential therapeutic effect as it can improve inflammatory response, uremic toxin, insulin resistance and cardiovascular risk.Conclusion: Prebiotic, probiotic, fecal microbiota transplantation and novel therapies have shown beneficial effects in treating patients with CKD.